Impact of the COVID-19 pandemic on the living conditions and physical functioning of community-dwelling older adults - Satoko Sasaki; Shigeru Ota; Kazuyoshi Takashima; Yoshiyasu Dezaki; Tomomi Sato; Yumi Sakogashira; Hitoshi Okamura (Journal of Family Medicine and Primary Care)
Background: The novel coronavirus disease 2019 (COVID-19) changed the lives of older adults as well as their activities, and these changes will likely impact their physical functioning. However, few reports have prospectively assessed the individual characteristics and pandemic-related changes associated with the living conditions and physical functioning of community-dwelling older adults or clarified the associated factors. This study evaluated the changes in the living conditions and physical functioning of community-dwelling older adults due to the COVID-19 pandemic and identified the associated factors. Methods: Forty-one community-dwelling older adults who met the eligibility criteria were surveyed before and after the first wave of the COVID-19 pandemic to assess their living conditions and physical functioning. The association between changes in physical functioning and the characteristics of older adults was examined using multiple regression analysis. Results: It was demonstrated that the number of participants who indicated that they rarely went out increased approximately threefold after the first wave of the pandemic. In addition, significant differences were found in 5-meter walking speeds (comfort speed) of participants after the first wave; however, the change was significantly lower for the group requiring nursing care than for the group requiring assistance. Conclusions: These results indicate that, given the increased number of homebound older adults due to the pandemic, more attention should be given to maintain physical functioning of older adults, specifically those requiring nursing care.